Horizontally Issuing Diffusion Flames Characterized by OH-PLIF and Visualizations. (March 2014) - Heffernen, J.J.; Hartsfield, C.R.; Reeder, M.F.; Polanka, M.D.
Planar laser induced fluorescence and flame visualizations characterized the effect of buoyancy on the behavior of the combustion zone of diffusion jet flames which issued from horizontally-oriented tubes into ambient air. The study focused on the mixing characteristics of propane and ethylene at Reynolds numbers ranging from 300 to 1500 in the near field of the jet (up to X/D=9) and Froude numbers ranging as low as 0.36, based on cold-flow gas properties and conditions. Performing the study with a variety of fuel tube diameters enabled independent control of Froude and Reynolds numbers. The PLIF visualizations revealed the presence of the hydroxyl radical in the mixing layer for all cases. The hydroxyl concentrations were consistently higher in the upper portion of the mixing layer, indicative of more vigorous mixing in this region. The visualizations also revealed the evolution of polycyclic aromatic hydrocarbons which were initially spatially segregated from the portion of the reaction zone containing the hydroxyl radical. The polycyclic aromatic hydrocarbons initiate in fuel-rich regions nearer to the jet core than the hydroxyl radical, though the two regions eventually combine well downstream of the tube exit. Both the hydroxyl radical and the polycyclic aromatic hydrocarbons were more prominent on the upper side of the jet flame. Both propane and ethylene fuels led to qualitatively similar features of the flow field, indicating the important role played by the buoyancy-influenced fluid dynamics of the combustion products. The resulting cross sectional PLIF images were used to produce a three-dimensional representation of the reaction zone, indicating the jet spread and trajectory. The data was empirically correlated and found to collapse when based on the Froude number consistent with the density and temperature of a fully-reacted stoichiometric mixture. Complementary visualizations provided additional insight into the trajectory of the jet flame and revealed features of the reaction zone farther from the tube exit.